Peran Dana Desa Dalam Peningkatan Ketahanan Lingkungan Di Provinsi Daerah Istimewa Yogyakarta - Ignatius Novianto Hariwibowo; Daniel Yudistya Wardhana (Seminar Nasional Penelitian dan Abdimas, 2023)
One of the objectives of channeling village funds to the village government is to improve village welfare through village development, one of which is environmental development as measured by the Environmental Resilience Index (IKL). Therefore, this study aims to evaluate the effectiveness of using village funds to increase IKL achievement. This study used a descriptive approach with secondary data on IKL values and realization of village funds, from villages in all villages in the Special Region of Yogyakarta (DIY), namely 392 villages. Data obtained from the Ministry of Village PDTT website were processed using the K-Means clustering algorithm, via Orange 3.35 software. The results of this study indicate that villages in DIY Province use village funds effectively to increase IKL.